Insights into different microwave-activated persulfate systems for chlorpyrifos degradation in soil: Impacts of soil properties, toxicity, and energy consumption - Xiao Shang; Li Gao; Zheng Sun; Zhenming Liang; Xitao Liu; Chunye Lin; Mengchang He; Wei Ouyang (Soil & Environmental Health)
Different microwave-activated persulfate (MP) systems exhibit considerable degradation efficiency towards chlorpyrifos in soil, a typical organophosphorus pesticide. However, only considering degradation efficiency cannot fully verify the effectiveness of MP systems in remediating chlorpyrifos-contaminated soil. Multiple evaluations, including soil characterization, toxicity assessment, and energy consumption estimation, were conducted to investigate the effectiveness of MP technologies. While the differences in soil morphology and structure were relatively small, soil dissolved organic matter varied with different MP treatments. Compared with parent compounds, the predicted toxicity of the degradation products was reduced. The acute toxicity and phytotoxicity of the solid phase reduced after the MP treatments, with the germination rate, and stem and root lengths of tall fescue being increased. However, the toxicity of residual oxidants in the liquid phase cannot be ignored, reducing ∼35% germination rate in ryegrass seed and luminescence intensity in bacteria. A constant microwave temperature was beneficial for degrading lower concentrations of chlorpyrifos, whereas constant microwave power was beneficial for degrading higher concentrations of chlorpyrifos. In short, the MP technology may be suitable for remediating chlorpyrifos-contaminated soil, and a comprehensive evaluation provides a theoretical basis for its practical application in soil remediation.